Afek Positif Sebagai Mediator dalam Hubungan antara Efikasi Diri dan Bias Atensi Emosional pada Remaja - Parahita, Aqillah Ridha; Handayani, Eko (Mahesa Research Center, 2023)
Emotional attention bias is an unconscious cognitive process that affects the processing of information. Individuals with positive emotional attention bias tend to have high self-efficacy. In adolescents, high self-efficacy helps them to get through difficult situations. This study seeks to find out the relationship between self-efficacy and emotional attention bias in adolescents by assuming there is a mediating role of positive affect. This is because the behavior and thoughts of adolescents are strongly influenced by affect. The purpose of this study was to examine positive affect as a mediator in the relationship between self-efficacy and emotional attention bias towards happiness and threats related words in adolescents. A total of 87 adolescent participants who were also high school students (M= 16.5) participated in this study. Self-efficacy was measured using the General Self-Efficacy Scale and positive affect was measured using the positive affect dimensions of the Positive Affect and Negative Affect Scale. Meanwhile, emotional attention bias was measured using the emotional Stroop task. The results using Jamovi's mediation showed that the relationship between self-efficacy and emotional attention bias towards happiness and threats related words was fully mediated by positive affect. This study succeeded in explaining the role of automatic and unconscious cognitive processes in the relationship between self-efficacy and emotional attention bias in adolescents.